Screening the genome of grapevine leafroll associated virus-2 for proteins with RNA silencing suppressor activity and the construction of a tandem silencing vector to induce simultaneous silencing of two genes - Engelbrecht, M. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2006.